Mechanisms Underlying the Interaction Between Chronic Neurological Disorders and Microbial Metabolites via Tea Polyphenols Therapeutics - Hong, Mengyu; Cheng, Lu; Liu, Yanan; Wu, Zufang; Zhang, Peng; Zhang, Xin (Frontiers in Microbiology, 2022)
The number of hydroxyl groups and existence of characteristic structural groups in tea polyphenols (TP) make them have antioxidant activity, which gives TP anti-inflammatory effects, toward protecting the intestinal flora and brain neurons. Host-associated microbial metabolites are emerging as dominant modifiers of the central nervous system. As yet, the investigations on host-microbiota crosstalking remain challenging, studies focusing on metabolites such as serotonin, short-chain fatty acids, and others have pinpointed multiple actionable signaling pathways relevant to host health. However, there are still complexities and apparent limitations inherent in transforming complex human diseases to corresponding animal models. Here, we choose to discuss several intestinal metabolites with research value, as crucial areas for assessing TP-mediated chronic brain diseases interactions with microbial.